Ground and Whole Grain Corn: Effect on Ruminal pH in Goats Diets - Arias, Rubén Omar (2015)
The objective of this study was to evaluate the effects of whole and ground corn grain in ruminal pH and total dry matter intake in diets for goats. Eight crossbreed goats (Creole x Nubian) was fitted with a rumen cannula and assigned in a replicated 4 x 4 Latin square experimental design. Two experiments were conducted; in the first test we used whole grain corn and second, ground corn grain. Ruminal pH data was measured for each goat as average pH, area between the curve and a horizontal line at pH 6, and duration less than pH 6 . In the first experiment, there were not differences (p> 0.05) on area between the curve and a horizontal line at pH 6, average pH and duration less than pH 6 among diets. A tendency was observed (p= 0.08) to decrease in DMI and the F/C decreased linearly (p< 0.05) with increasing whole corn in ration. In the second experiment, a significant linear increase was observed (p< 0.05) on area between the curve and a horizontal line at pH 6, with increasing ground corn. A linear decrease (p <0.05) was observed in average ruminal pH and linear increase (p <0.05) in duration less than pH 6. There was no difference in DMI and linear decrease (p <0.05) in F/C with increasing whole. The milling corn grain, increase the hydrolysis rate of the starch, possibly because to increased bacterial colonization of the horny endosperm surface, lowering ruminal pH.